Special Agricultural Safeguards : Virtual Benefits and Real Costs-Lessons for the Doha Round - Hallaert, Jean-Jacques (IMF Working Papers; Working Paper ;, 2005)
In the Doha Round, negotiators are discussing the elimination or continuation of the special agricultural safeguards introduced by the Uruguay Round as well as the creation of special safeguard mechanism for use by developing countries. This paper argues that, in violation of the spirit of the WTO Agreement in Agriculture, the special agricultural safeguards have often been used as a prolonged protectionist device. It then draws lessons for the design of the special safeguard mechanism.